Designing Interactive Video in English Writing Materials for Seventh Graders - Felicia Azzahra Kusdinar; Ratna Dewanti; Ilza Mayuni; Dieni Nurhasanah (International Journal of Education, Language, Literature, Arts, Culture, and Social Humanities, 2023)
Problems in learning writing did not seem to find a bright spot in education. Teachers tried to find solutions by evaluating learning materials and learning media. Recently, the solution of the writing problem had become a major concern. Thus, this research aimed to design technology-based learning materials referred to interactive videos with target learner seventh graders. This methodology used design development research (DDR). Data were sourced from junior high schools in Jabodetabek. The main data for designing were the results of the analysis learning materials, learning objectives, and interview result with teacher. The design of interactive video paid attention to the main aspects including the characteristics of interactive video, learning objectives, and students' needs. In addition, time efficiency was also important to maintain students' motivation in learning. Through interactive video, students' engagement in interacting with the learning content was the key to successful learning. Therefore, the result of this design showed this media has high potential to be implemented in writing class.